Python : penetration testing for developers : unleash the power of Python scripting to execute effective and efficient penetration tests : a course in three modules.: penetration testing for developers : unleash the power of Python scripting to execute effective and efficient penetration tests : a course in three modules. (2016) - Duffy, Christopher
No abstract available